SOME INFORMATION ON THE HISTORY OF THE STUDY OF ANCIENT ALTAI - Choriyeva Nargiza Ibotovna; Qurbonov Sherzod Farhodovich (European Science Publishing, 2024)
Since the Altai territory is not only one of the most beautiful, but also has a rich history, the study of its history was of interest to researchers. This article provides some information on the history of ancient Altai learning.
Keywords: civilization, archaeological culture, prospectors, expedition.